Folliculosebaceous Cystic Hamartoma with Spindle Cell Lipomatous and Neural Components - Carmelo Urso; Marina Yarygina (MDPI AG, 2023)
Folliculosebaceous cystic hamartoma is a cutaneous malformation composed of a cystic folliculosebaceous structure associated with mesenchymal elements, generally consisting of fibrous stroma, adipocytes and small vascular channels. We report the case of a 55-year-old female patient with a cutaneous nodule of the right nasal wing. Microscopically, the lesion showed a dilated hair follicle with multiple sebaceous glands, surrounded by a mesenchymal component composed of fibromyxoid stroma, spindle cells, mature-appearing adipocytes and collagen bundles, resembling spindle cell lipoma, associated with an additional neural component, consisting of small nerve bundles. In folliculosebaceous cystic hamartoma, the association of spindle cell lipomatous and neural components has not previously reported.